2020
DOI: 10.1016/j.tips.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Structural Features of TSPO: Implications for Drug Development

Abstract: The translocator protein (TSPO), an 18-kDa transmembrane protein primarily found in the outer mitochondrial membrane, is evolutionarily conserved and widely distributed across species. In mammals, TSPO has been described as a key member of a multiprotein complex involved in many putative functions and over the years several classes of ligands have been developed to modulate these functions. This review considers the currently available atomic structures of mouse and bacterial TSPO and proposes a rationale for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…The drug ligand binding domains of TSPO have been mapped [87] and it was subsequently shown that TSPO is a highaffinity cholesterol binding protein containing a conserved cholesterol recognition amino acid consensus domain in the C-terminus [88,89]. The drug and cholesterol binding domains were found to be in distinct domains of the protein results confirmed by NMR [87,88,90].…”
Section: Molecular Structure and Cellular Functionsmentioning
confidence: 91%
“…The drug ligand binding domains of TSPO have been mapped [87] and it was subsequently shown that TSPO is a highaffinity cholesterol binding protein containing a conserved cholesterol recognition amino acid consensus domain in the C-terminus [88,89]. The drug and cholesterol binding domains were found to be in distinct domains of the protein results confirmed by NMR [87,88,90].…”
Section: Molecular Structure and Cellular Functionsmentioning
confidence: 91%
“…Structural studies of bacterial TSPO showed that PPIX binds to the same site to which PK 11195 binds [Guo et al, 2015;Li et al, 2015]. The binding cavity changes to adapt to various ligand [Lacapere et al, 2019]. It has been described that ALA has a very low affinity for TSPO1 in the millimolar range In the cytosol, the cyclic tetrapyrrole, coproporphyrinogen III, is formed from ALA in a series of four enzymatic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Improved insights into the key structural features of TSPO that influence ligand binding and its function under pathological conditions will also guide medicinal chemists in their attempts to rationally design drugs that have potent and predictable neuroprotective effects. [65] For those of us focusing our efforts on targeting TSPO, there are undoubtedly more adventures ahead.…”
Section: Summary and Future Directionsmentioning
confidence: 99%